Persistence and transience of food insecurity and predictors among residents of two disadvantaged communities in South Carolina - Liese, Angela D. (Appetite, 2021)
BACKGROUND: Little is known about patterns of household food insecurity (HFI) across more than two time points in adults in the United States, the frequency predictors of different trajectories. The distinctions between persistent and transient food insecurity trajectories may be crucial to developing effective interventions. OBJECTIVE: To characterize dominant trajectories of food security status over three time points between 2013 and 2016 and identify demographic, socioeconomic and health-related predictors of persistent and transient HFI. DESIGN: Cohort study in disadvantaged communities in South Carolina. SETTING AND SUBJECTS: 397 middle-aged participants, predominantly female, African American, living in USDA-designated food deserts. MAIN OUTCOME MEASURE: Household food insecurity over time using the 18-item USDA’s Household Food Security Survey Module. STATISTICAL ANALYSES PERFORMED: Descriptive analyses of food security trajectories and multinomial regression analyses. RESULTS: At baseline (2013–2014), 61% of households reported HFI during the previous 12 months, which decreased to 54% in 2015 and to 51% in 2016. Only 27% of households were persistently food secure, 36% experienced transient and 37% persistent food insecurity. Female sex (OR 2.7, 95%CI 1.2–5.9), being married or living with a partner (OR 2.4, 95CI% 1.1–5.3) and fair health status (OR 4.4, 95%CI 2.2–8.8) were associated with increased odds of persistent food insecurity. Fair health was also a significant predictor of transient food insecurity. CONCLUSIONS: These findings suggest that future research should focus on persistent versus transient trajectories separately and that tailored interventions may be needed to make progress on alleviating food insecurity among disadvantaged communities.